Emi isn't scared of monsters - Tysoe, Alina (New York : Orchard Books, an imprint of Scholastic Inc., 2022)
Emi is not afraid of the dark and whatever monsters patrol the halls of her home--in fact she has a plan and the equipment to catch them (if only she can stay awake).
Ages 4-8.
Grades K-1.
Keywords: Monsters -- Juvenile fiction; Courage -- Juvenile fiction; Humorous stories; Monsters -- Fiction; Fear of the dark -- Fiction; Humorous stories; Humorous fiction